Energy-Dependent Chemical Potentials of Light Hadrons and Quarks Based on Transverse Momentum Spectra and Yield Ratios of Negative to Positive Particles - Xing-Wei He; Feng-Min Wu; Hua-Rong Wei; Bi-Hai Hong (Advances in High Energy Physics)
We describe the transverse momentum spectra or transverse mass spectra of π±, K±, p, and p¯ produced in central gold-gold (Au-Au), central lead-lead (Pb-Pb), and inelastic proton-proton (pp) collisions at different collision energies range from the AGS to LHC by using a two-component (in most cases) Erlang distribution in the framework of multisource thermal model. The fitting results are consistent with the experimental data, and the final-state yield ratios of negative to positive particles are obtained based on the normalization constants from the above describing the transverse momentum (or mass) spectra. The energy-dependent chemical potentials of light hadrons (π, K, and p) and quarks (u, d, and s) in central Au-Au, central Pb-Pb, and inelastic (pp) collisions are then extracted from the modified yield ratios in which the contributions of strong decay from high-mass resonance and weak decay from heavy flavor hadrons are removed. The study shows that most types of energy-dependent chemical potentials decrease with increase of collision energy over a range from the AGS to LHC. The curves of all types of energy-dependent chemical potentials, obtained from the fits of yield ratios vs. energy, have the maximum at about 3.510 GeV, which possibly is the critical energy of phase transition from a liquid-like hadron state to a gas-like quark state in the collision system. At the top RHIC and LHC, all types of chemical potentials become small and tend to zero at very high energy, which confirms that the high energy collision system possibly changes completely from the liquid-like hadron-dominant state to the gas-like quark-dominant state and the partonic interactions possibly play a dominant role at the LHC.